REDUKSI LOGAM BERAT CHROMIUM (VI) DENGAN FOTOKATALIS KOMPOSIT TiO2-SiO2 - Purnawan, Candra (Bumi Lestari, 2013)
Abstracts Composite TiO2-SiO2 has been synthesized using sol-gel process with starting materials TiCl4 and Na2SiO3. The purposes of this research were to know the effect of composite composition, pH solution and UV radiation time for reduced Chromium (VI) cations. The identification and characterization of composite were done by infrared spectroscopy (IR) and X-Ray Diffraction. Condition of Chromium (VI) reduction by composite TiO2-SiO2 were carried out with variation of composite TiO2-SiO2 concentration or the ratio Ti:Si were 1:0,1 ; 1:0,5 ; 1:1 ; 1:1,5 ; 1:2. Variation of pH solution in 3,0; 3,5; 4,0; 4,5; 5,0; 5,5; 6,0; 6,5; 7,0 and variation of UV radiation times in 2, 4, 6, 12, 18, 24, 30, 36, 42, 48 hours. The result showed that XRD characteristic of TiO2-SiO2 composite showed 2q peaks at 22.94 degrees and 36.24 degrees. IR characteristic of TiO2-SiO2 showed absorption of Ti-O-Si in the wave number 962 cm-1. The optimum reduction of Chromium (VI) cations using TiO2- SiO2 composite in Ti:Si = 1:1 composition, pH 3 and with 18 hours radiation times.
Keywords: Keywords: composite TiO2-SiO2, reduction of Chromium (VI), SiO2 concentration, pH, and radiation time